Testicular biometry and its correlation with body weight and semen output in Murrah bull - Kumar, Sanjeet; Srivastava, Sushant (Buffalo Bulletin, 2017)
The present study was conducted to find out testicular biometry and its correlation with body weight, scrotal circumference semen production. Semen sample were collected from six sexually mature Murrah buffalo bulls, aged 4 to 12 years, maintained in bull station of College of Veterinary Sciences and Animal Husbandry, Kumarganj, Faizabad, Uttar Pradesh, India. Biometrical evaluation was performed by caliper in all experimental bulls. The biometric testicular parameters (scrotal circumference, testicular length, testicular width and testicular volume) were analyzed. Present findings indicate strong correlations between scrotal circumference, testicular volume and body weight. The body weight was significantly (P < 0.01) and positively correlated with scrotal circumference (r=0.98), testicular volume (r=0.97), sperm concentration (r=0.94), concentration/ ejaculate (r=0.64), initial motility (r=0.90), live count (r=0.89), whereas it was significantly (P < 0.01) negatively correlated with total sperm abnormality (r=-0.79). The overall mean (±SE) scrotal circumference of Murrah bulls were ranges between 31.02±0.39 to 46.33±0.43 cm. A significant (P < 0.01) variation in S.C. was reported among the bulls. The scrotal circumference was significantly (P < 0.01) and positively correlated with body weight (r=0.98), testicular volume (r=0.96), testicular parenchyma (r=0.98), sperm concentration (r=0.91), concentration/ejaculate (r=0.63).